2009
DOI: 10.1179/174328408x259052
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and high temperature strength of age hardenable AA2219 aluminium alloy modified by Sc, Mg and Zr additions

Abstract: In the present work, it was envisaged to develop thermally stable Al–Cu alloy by modifying its chemistry. AA2219 alloys with different levels of scandium (Sc), magnesium (Mg) and zirconium (Zr) were prepared by melting with inert gas (argon) tungsten arc welding. Sc was added in three levels (0·2, 0·4, 0·8%), Mg one level (0·45%) and Zr one level (0·2%). Optical, scanning electron microscopy (SEM), X-ray diffractometry (XRD) and transmission electron microscopy (TEM) were carried out to study the microstructur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The increase in micron-sized T (Al 20 Cu 2 Mn 3 ) and nano-sized α-Fe precipitates can be mainly attributed to grain refinement [32]. It has been reported that the grain size can influence the amount and size of precipitates in Al–Cu alloys [59,60], which is due to that the refined grains lead to a shorter diffusion distance of Cu, Mn, Fe, and Si atoms during solution treatment [19]. Therefore, during solution treatment, Cu, Mn, Fe, and Si atoms are more homogeneously distributed, resulting in the simultaneous nucleation of a larger number of precipitates.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase in micron-sized T (Al 20 Cu 2 Mn 3 ) and nano-sized α-Fe precipitates can be mainly attributed to grain refinement [32]. It has been reported that the grain size can influence the amount and size of precipitates in Al–Cu alloys [59,60], which is due to that the refined grains lead to a shorter diffusion distance of Cu, Mn, Fe, and Si atoms during solution treatment [19]. Therefore, during solution treatment, Cu, Mn, Fe, and Si atoms are more homogeneously distributed, resulting in the simultaneous nucleation of a larger number of precipitates.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, iron is one of the primary alloying elements in heat-resistant aluminium alloys. For instance, iron is added to increase the strength of Al-Cu-Mg-Fe-Ni alloys, such as AA2219 and AA2618, at elevated temperatures [18,19]. Therefore, despite the need for iron impurity control, it is a very economical way to develop high-performance heat-resistant aluminium alloys using recycled aluminium.…”
Section: Introductionmentioning
confidence: 99%
“…The addition of 1.6-2.0 wt % Li also shows excellent mechanical properties for AA2099 (Al-Cu-Li) alloys at high temperature, primarily due to the enhanced thermal stability of T 1 (Al 2 CuLi) precipitates compared to other possible strengthening precipitates like θ 0 and S (Al 2 CuMg) [41]. At higher temperature, T 1 precipitates coarsen instead of dissolving unlike θ 0 or S. In addition, AA2219 alloy possesses improved high temperature performance when micro-alloyed with 0.8 wt% Sc, 0.45 wt% Mg and 0.2 wt% Zr from grain refinement and simultaneous precipitation of Al 3 Sc, Al 3 Zr and Ω precipitates along with other common strengthening precipitates like θ 0 and θ″ [42].…”
Section: Attempts Towards the Development Of High Temperature Aluminu...mentioning
confidence: 99%